(untitled) (Vietnam Journal of Community Medicine, 2024)
Objective: To describe the clinical and paraclinical features of pre-eclampsia, eclampsia women at A Thai Nguyen Hospital and pregnancy outcomes. Subject and method: A cross-sectional descriptive study on 67 pregnant women are diagnosed with preeclampsia, eclampsia and treatment at A Thai Nguyen Hospital from April -2022 to April - 2023. Survey of clinical and subclinical characteristics appearing during treatment, including symptoms of the disease, reflecting multi-organ damage related to preeclampsia - eclampsia. Pregnancy outcomes include time, method of termination of pregnancy and complications on mother and child. Results: The overall preeclampsia - eclampsia rate was 1,28% of which 0.4% were preterm and 0.54% were severe. 32.8% of pre-eclampsia cases had signs of edema, 38.5% of preeclampsia cases have blood pressure values < 140/90 mmHg and severe preeclampsia groups have 60.7% of cases have blood pressure values >160/110 mmHg. The uric acid concentration in the severe pre-eclampsia group (402,6 + 78,6 µmol/l) was statistically significantly higher than in the group without severe signs (342,6 + 80,2 µmol/l), p < 0.05. The rate of cesarean section was 86.5%, this rate was 95.2% in the severe pre-eclampsia group. Eclampsia and perinatal mortality accounted for 1.5% and both occurred in severe preeclampsia groups. Conclusion: The rate of preeclampsia - eclampsia in A Thai Nguyen hospital is relatively low. However, the rate of cesarean section in this group of patients is quite high, especially in the group with severe disease. Preterm birth rate, rate complications were all adverse in the severe preeclampsia group.